2007
DOI: 10.1091/mbc.e06-08-0685
|View full text |Cite
|
Sign up to set email alerts
|

Function of theCaenorhabditis elegansABC Transporter PGP-2 in the Biogenesis of a Lysosome-related Fat Storage Organelle

Abstract: Caenorhabditis elegans gut granules are intestine specific lysosome-related organelles with birefringent and autofluorescent contents. We identified pgp-2, which encodes an ABC transporter, in screens for genes required for the proper formation of gut granules. pgp-2(-) embryos mislocalize birefringent material into the intestinal lumen and are lacking in acidified intestinal V-ATPase-containing compartments. Adults without pgp-2(+) function similarly lack organelles with gut granule characteristics. These cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(180 citation statements)
references
References 84 publications
5
174
1
Order By: Relevance
“…The discrepancy between the Nile red staining and the three other methods used to monitor lipid stores, i.e., CARS microscopy, Sudan black, and gas chromatography, point to some limitation of the Nile red staining method as an indicator of lipid store status in C. elegans. Indeed, others have shown that Nile red merely stains lysosome-related compartments in C. elegans (22,37), and our results also show that Nile red allows the visualization of only a subset of the lipid droplets. There are obviously a variety of gut granules types in the C. elegans intestine, of which only a subset is stained by Nile red, and staining of this subset by Nile red does not always correlate with lipid content.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The discrepancy between the Nile red staining and the three other methods used to monitor lipid stores, i.e., CARS microscopy, Sudan black, and gas chromatography, point to some limitation of the Nile red staining method as an indicator of lipid store status in C. elegans. Indeed, others have shown that Nile red merely stains lysosome-related compartments in C. elegans (22,37), and our results also show that Nile red allows the visualization of only a subset of the lipid droplets. There are obviously a variety of gut granules types in the C. elegans intestine, of which only a subset is stained by Nile red, and staining of this subset by Nile red does not always correlate with lipid content.…”
Section: Discussionsupporting
confidence: 70%
“…To monitor protein prenylation in C. elegans, we adapted a GFP-based method previously described for mammalian cells (41). The plasmid pGLO-1P::GFP-CAAX carries the intestinal-specific promoter glo-1 (22,42) to express a modified GFP fused to the last 12 aa of the C. elegans ras-2 gene, including the terminal prenylation motif sequence CLIS (see SI Materials and Methods). pGLO-1P::GFP-CAAX was microinjected together with the phenotypic marker rol-6 carried on plasmid pRF4 (43), and transgenic worms were maintained by picking individuals with the roller phenotype.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations, together with our observation that sup-37 is expressed strongly in the larval pharynx (see below), suggested that sup-37 null mutants may have defective pharynges that preclude proper feeding. Consistent with a feeding defect, the intestines of the mutants have refractile vacuoles indicative of starvation (Schroeder et al 2007). To test this, homozygous tm356 and tm1083 mutants were fed fluorescent Escherichia coli (OP50) and analyzed by compound microscopy.…”
Section: Sup-37 Is Required For Normal Pharyngeal Pumpingmentioning
confidence: 98%
“…Upon RNAi knockdown of cua-1, the number and morphology of LysoTracker-positive compartments did not change. However, RNAi knockdown pgp-2, which encodes an ABC transporter that is required for gut granule biogenesis and localizes to the gut granule membrane (35,37), significantly reduced LysoTracker staining and prevented CUA-1.1::GFP-containing vesicle formation, whereas CUA-1.1::GFP was detected on the basolateral membrane (Fig. 6A).…”
Section: Cua-11 Is Required For Copper Detoxification In Intestine-mentioning
confidence: 99%